SKELETAL MUSCLE PERFUSION IN POST-EXERCISE HYPEREMIA IN YOUNG AND OLD ADULTS AS ASSESSED BY DIFFUSION-WEIGHTED MRI. (11th November 2018) - Adelnia, F; Shardell, M; Bergeron, C; Fishbein, K; Spencer, R; Reiter, D; Ferrucci, L
Abstract: Aging is associated with impaired endothelium-dependent vasodilation that contributes to organ dysfunction and progression of cardiovascular disease. Impaired muscle perfusion results in inadequate adaptation to oxygen and nutrient demands during and after muscle contraction, limiting performance. Accurately measuring muscle perfusion is essential for understanding mechanisms by which aging contributes to declining physical function. Therefore, we developed and validated a non-invasive diffusion-weighted MRI (DW-MRI) technique to characterize perfusion and diffusivity of water molecules in skeletal muscle in response to exercise. The mid-thigh of the left leg of four younger (21–30 year-old) and four older (60–90 year-old) healthy female volunteers was studied using DW-MRI at rest (baseline) and at 7 time points following in-magnet knee extension exercise with a temporal resolution of 3.25min. Exercise was performed using a MR-compatible ergometer with a workload of 0.4bar for 2.5min. After exercise, both perfusion and diffusivity significantly increased from baseline with a peak at the second dynamic in rectus femoris (active during exercise) compared to medial adductor (inactive) in both age groups, reflecting the local increase in blood flow. However, different time-courses of perfusion were observed in younger versus older groups following exercise. A significantly steeper (p<0.05) and greater hyperemia was observed in the younger group (37 ± 12.05%) compared to the older group (17.57 ± 15.92%) at the first post-exercise measurement. Similarly, a slower return toward baseline was also observed in the rectus femoris in the older group compared with the younger group. This work establishes a valid non-invasive method that can quantify muscle perfusion in aging studies.